60. EVALUATION OF THE EFFECTIVENESS OF BLOOD FILTRATION THROUGH THE KT/V INDEX IN PATIENTS ON PERIODS OF BLOOD FILTRATION AT THE NGE AN GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Currently, in developing countries, the reuse of dialyzers to reduce the cost of hemodialysis is common. The Kt/V index is used to evaluate the effectiveness of dialysis sessions.Objective: To investigate the correlation between the automatically displayed Kt/V value on the hemodialysis machine (OCM) and the Kt/V values calculated using the Daugirdas and Lowrie formulas in patients undergoing maintenance hemodialysis.Method: A prospective descriptive study was conducted on all hemodialysis patients at the Nephrology Department of Nghe An General Friendship Hospital who met the inclusion criteria.Results: The mean age of the patients was 49.92 ± 15,55 years. The proportion of patients achieving the recommended Kt/V decreased progressively according to the Daugirdas, OCM, and Lowrie formulas (p < 0.001). Kt/V values measured by OCM showed a downward trend over successive dialysis sessions (p < 0.001). The correlation coefficient between Kt/V measured by the machine and calculated by the Daugirdas formula was R = 0.843.Conclusion: The Kt/V index tended to decrease with an increasing number of dialyzer reuses. The Kt/V measured by the OCM module showed a strong correlation with the Daugirdas formula and may serve as a reliable alternative for evaluating the adequacy of maintenance hemodialysis..
Keywords: Maintenance hemodialysis,Kt/V, Daugirdas